Antimicrobial Potential of Grape Seed Extract and MTA: A Comparative Experimental Study - Elgendi, Huda; Hamdy, Mai (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to evaluate and compare the antibacterial potential of mineral trioxide aggregate (MTA) and grape seed extract (GSE) against Streptococcus mutans, Enterococcus faecalis, Staph aureus, Candida albicans, Lactobacillus spp., and Streptococcus sobrinus. HYPOTHESIS: We hypothesized that GSE could have potent antimicrobial effect against oral pathogens when compared to MTA. MATERIALS AND METHODS: MTA and GSE were utilized to determine the antibacterial effectiveness against S. mutans, E. faecalis, S. aureus, C. albicans, Lactobacillus spp. and S. sobrinus using the agar well diffusion test. The tested materials were used according to the manufacturer’s instructions and put into the prepared wells of agar plates; diluted inocula (105 and 106 CFU/ml) of the tested microorganism strains were also used. For bacteria, all plates were incubated at 37°C in anaerobic conditions, and for C. albicans, at 30°C. The inhibitory zones were determined after 3 days. A digital caliper was used to measure the diameter of bacterial inhibition zones surrounding each well to the nearest size in mm. RESULTS: GSE-created inhibition zones against all tested microorganisms except C. albicans, zones were significantly larger than MTA-created zones (p < 0.05). CONCLUSION: Both MTA and GSE showed antimicrobial effect against all tested microorganisms except C. albicans, which will pave the route to use GSE as a natural herbal substitute of MTA.